2021
DOI: 10.1177/21582440211032202
|View full text |Cite
|
Sign up to set email alerts
|

Risk as an Approach to Regulatory Governance: An Evidence Synthesis and Research Agenda

Abstract: Governments around the world have begun to develop and implement risk governance and risk-based regulation and are often inspired by the insights from risk studies in doing so. Following these developments, scholars have begun to map, explore, and interrogate risk governance models and strategies and risk-based regulatory approaches and instruments, and their performance. This article presents an evidence of academic literature on risk as an approach to regulatory governance. It follows the logic and applies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…It is essential to be aware of the possible mismatch between the rhetoric on the value of systems thinking for and in regulatory governance and the application of this approach in regulatory scholarship and practice. As in other areas of regulatory governance (Van der Heijden, 2021a), there is considerably more theorizing on how systems thinking may improve the (cost-)effectiveness of regulatory governance (i.e., utilitarian motivations for its application) and its transparency and accountability (i.e., political or moral motivations for its application) than there is evidence that these expectations are met. The narrative review has indicated an ongoing and substantial interest in systems thinking for and in regulatory governance; the evidence synthesis has indicated that we know little about how, where, and with what effects it is applied in regulatory practice.…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…It is essential to be aware of the possible mismatch between the rhetoric on the value of systems thinking for and in regulatory governance and the application of this approach in regulatory scholarship and practice. As in other areas of regulatory governance (Van der Heijden, 2021a), there is considerably more theorizing on how systems thinking may improve the (cost-)effectiveness of regulatory governance (i.e., utilitarian motivations for its application) and its transparency and accountability (i.e., political or moral motivations for its application) than there is evidence that these expectations are met. The narrative review has indicated an ongoing and substantial interest in systems thinking for and in regulatory governance; the evidence synthesis has indicated that we know little about how, where, and with what effects it is applied in regulatory practice.…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…16 Indeed, in recent decades, risk as an approach to public governance and regulation has, in general, gathered increasing momentum across all Western countries. 17 In the UK, as highlighted by Black, risk management had already become a key feature in developing regulation during the first decade of the 21st century. 18 The same process has recently affected EU law as well.…”
Section: Introductionmentioning
confidence: 99%